HADIS-HADIS DALAM KITAB HIDÄ€YAH AL-SÄ€LIKÄªN (Kajian Sanad dan Matn) - Sagir, Akhmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ine"> </This paper provides an overview and explanation relating to the qualityof the existing 190 hadiths in HidÄyah al-SÄlikÄ«n of Sheikh Abdus Samadal-Palembani and 51 hadiths added by Shamsuddin Siddiq in the editedbook. This research is signifiant to answer the doubts about the quality ofexisting hadiths in this book, while this book is very popular and used asa reference in a large community. The study shows that the book consists ofdifferent quality of hadiths from sahih, hasan, dhaif and mawdu.â€™